2014
DOI: 10.1111/are.12520
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate and propionate improve the growth performance ofLitopenaeus vannamei

Abstract: Organic salts may improvement the animal performance, increasing the efficiency of nutrient utilization and modifying the intestinal microbiota. This study aimed to evaluate the effects of sodium butyrate and sodium propionate supplementation at different levels of dietary inclusions in the growth of Litopenaeus vannamei. In total, seven diets were evaluated: a control diet (without supplementation) and three diets from each sodium salt, propionate and butyrate, in concentrations of 0.5%, 1% and 2%. We used 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 39 publications
5
102
0
Order By: Relevance
“…In another study of shrimp reared in clear water, Silva et al () observed that a diet supplemented with sodium butyrate increased the growth and survival of L . vannamei .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study of shrimp reared in clear water, Silva et al () observed that a diet supplemented with sodium butyrate increased the growth and survival of L . vannamei .…”
Section: Resultsmentioning
confidence: 99%
“…In the clear‐water rearing of L . vannamei , dietary supplementation with 0.5 and 2% of sodium butyrate increased the retention of nitrogen and the rate of protein efficiency, but phosphorus was not retained (Silva et al ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic acids or their salts are capable of inhibiting the growth of harmful intestinal microorganisms such as coliforms, enterococci and vibrio sp. (Øverland et al., ; Zhou et al., ; Silva et al., ) and promoting the reproduction of acid tolerant beneficial bacteria such as Lactobacilli (Luckstadt, ), which may ultimately increase the digestive enzyme activities of the fish intestine (Askarian et al., ).…”
Section: Discussionmentioning
confidence: 99%